A Fluorescence-Based High-Throughput Assay for the Identification of Anticancer Reagents Targeting Fructose-1, 6-Bisphosphate Aldolase. (January 2018) - Cho, Eun Jeong; Devkota, Ashwini K.; Stancu, Gabriel; Edupunganti, Ramakrishna; Powis, Garth; Dalby, Kevin N.
A high rate of glycolysis, which supplies energy and materials for anabolism, is observed in a wide range of tumor cells, making it a potential pathway to control cancer growth. ALDOA is a multifunctional enzyme in the glycolytic pathway and also promotes HIF-1α, which is of importance in hypoxic solid tumors. The current method for assaying ALDOA activity involves monitoring the consumption of NADH in vitro using absorbance or intrinsic fluorescence via a coupled enzymatic reaction. Here, we report the development of a homogeneous biochemical assay that can overcome limitations of current methods, in particular for the application of high-throughput drug screening. The assay utilizes the commercially available Elite NADH Assay Kit, which incorporates an enzymatic reaction to measure the level of NADH using a fluorescent probe. Assay optimization and validation are discussed. Its feasibility for high-throughput screening (HTS) was demonstrated by screening 65, 000 compounds for the identification of small molecules that inhibit ALDOA. Through a validation screen and dose–response evaluation, four inhibitors with IC50 below 10 µM were identified. In conclusion, we demonstrate that a traditional ALDOA assay can be transformed readily into a fluorescence-based assay utilizing a commercial NADH detection kit that is rapid, sensitive, inexpensive, and HTS friendly.